(untitled) (ModaPalavra e-periódico, 2014)
The ecologic fashion and sustainable fashion are two currents resulting from the joining of fashion and ecology, and work toward solutions to make the fashion industry less aggressive to the environment. The growing number of fans of both actions provided a setting for the emergence of new markets, in particular, organic materials, sustainable techniques, reuse and materials recycling. Moreover, had caused a phenomenon of worried consumption with the future, however, lay about basic fundamentals and concepts of eco-fashion, which gave rise to numerous "popular beliefs" about the subject, theories based on social perceptions, or media, without scientific evidence. As a result, there were liars products, brands leveraging the momentum of the market started taking the outdoors just as an advertising slogan, which discourages and harms regarding the strength that comes from winning this movement in fashion.